Severe cardiac valvular calcification in two Chinese brothers with mandibuloacral dysplasia type A: a case report - Guo, Yi; Zhang, Xinyi; Meng, Yanfei; Guo, Qiuzhe; Wang, Xiaoqi (Frontiers in Cardiovascular Medicine, 2025)
Mandibuloacral dysplasia type A (MADA) is a rare progeroid syndrome associated with mutations in the Lamin A/C (LMNA) gene, primarily affecting skeletal, cutaneous, and adipose tissues. While certain LMNA gene mutations are known to cause cardiomyopathy and conduction system disease, severe early-onset calcific valvular heart disease is not conventionally considered a typical feature of MADA. This report describes two brothers from a consanguineous Han Chinese family who presented with classical MADA phenotypes alongside severe, early-onset cardiac valvular calcification. Genetic investigation revealed that both affected brothers carried a homozygous missense mutation, c.785A > G (p.Glu262Gly), in the LMNA gene. The elder brother, aged 41, successfully underwent transcatheter aortic valve implantation (TAVI) due to severe aortic valve stenosis. This finding represents the first association, to our knowledge, between the homozygous LMNA c.785A > G (p.Glu262Gly) mutation and significant severe early-onset cardiac valvular calcification manifesting as a prominent feature within the MADA phenotype, thus expanding the clinical spectrum associated with MADA and this specific LMNA variant. This case highlights a potentially underrecognized cardiovascular manifestation in MADA patients and underscores the importance of comprehensive cardiac assessment in affected individuals, particularly those from consanguineous families.